2015
DOI: 10.3109/13880209.2015.1089911
|View full text |Cite
|
Sign up to set email alerts
|

Protection of SAL B with H9C2 cells

Abstract: Context: Salvianolic acid B (Sal B) is regarded as a potent antidiabetic agent and has been reported to possess cardioprotective effect in vivo. Objective: This study investigated the cardioprotective effects of Sal B on H9c2 cells injury caused by high glucose in vitro, and clarified the possible mechanisms. Materials and methods: Di ferent concentrations of Sal B were incubated with cells for 12 h prior being exposed to high glucose for 24 h. Cardioprotective effects of Sal B were evaluated using CCK-8 assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It is frequently found in potentially immunomodulatory substances that are active in vitro, however, its effects do not appear to be translatable to an in vivo system [17]. In the present research, the in vitro anti-inflammatory potential of SalB was mediated by a reduction of TNF from macrophages, which is in accordance with the study of Sun et al (2016), who also showed that SalB downregulated TNF secretion [18]. Macrophages also downregulated their NO production after SalB treatment.…”
Section: Discussionsupporting
confidence: 89%
“…It is frequently found in potentially immunomodulatory substances that are active in vitro, however, its effects do not appear to be translatable to an in vivo system [17]. In the present research, the in vitro anti-inflammatory potential of SalB was mediated by a reduction of TNF from macrophages, which is in accordance with the study of Sun et al (2016), who also showed that SalB downregulated TNF secretion [18]. Macrophages also downregulated their NO production after SalB treatment.…”
Section: Discussionsupporting
confidence: 89%
“…This anti-apoptotic effect involves the regulation of relevant signaling pathways during myocardial I/R damage, including the PI3K/Aktdependent [287] and SAPK signaling pathways [283] . Additionally, the cardioprotective effects of Sal-B against myocardial I/R injury have also been attributed to its anti-oxidant and antiinflammatory properties [286,288,293] . Moreover, Sal-B suppresses autophagy by upregulating miR-30a to improve cardiomyocyte viability during myocardial I/R damage [285,294] .…”
Section: Salvianolic Acid Bmentioning
confidence: 99%
“…The active components of S. miltiorrhiza are divided into two groups, one of which is water-soluble phenolics including salvianolic acid A (Sal A), salvianolic acid B (Sal B), lithospermic acid, rosmarinic acid, and R-(+)-β-(3,4-dihydroxyphenyl)lactic acid, named danshensu [ 3 ] and the other is lipophilic tanshinones including tanshinone I, tanshinone IIA, tanshinone IIB, cryptotanshinone, and dihydrotanshinone I [ 4 ]. Salvianolic acids (including Sal A and Sal B), the most abundant compounds from S. miltiorrhiza , are known to exhibit diverse biological activities such as antioxidant [ 5 ], anti-inflammatory [ 6 ], antithrombotic [ 7 ], and cardioprotective activities [ 8 , 9 ], while tanshinones show antitumor [ 10 ], cardioprotective [ 11 ], neuroprotective and analgesic activities [ 12 ], and so forth.…”
Section: Salvia Miltiorrhiza Bungementioning
confidence: 99%